Isolation and analysis of heavy metal-resistant bacteria originating from a stream contaminated with waste effluent from a paper recycling plant - Liew,, Pauline Woan Ying. (Universiti Malaysia Sarawak (UNIMAS), 2003)
A total of 404 heavy metal resistance bacterial isolates belonging to 10 gene were isolated from water and sediment samples taken at sites near a waste discharge point of a paper recycling mill in Sarawak. The resistance properties screend were CoR (400 ug/mg), NiR (1600 ug/mg), PbR (1400 ug/ml, CuR(1600 ug/ml) and AgR (25 ug/ml). Among the strains identified were Aeromonas hydrophila / caviae, Aeromonas salmonicida, Aeromonas sp.,Citrobacter freundii, Enterobacter annigenus, Enterobacter cloacae, Enterobacter sakazakii, Escherichia coli, Listonella damsela, Providencia alcalifaciens, Providencia sp., Psedomonas cepacia, Pseudomonas fluorescens/[utida, Pseudomonas sp., Serratia marcescens, Serratia rubidaea, Vibrio metschnikovii and Yersinia pestis. Multiple heavy metal resistance phenotypes (resistance towards 2 to 5 heavy metal) were observed in ~50% of the isolated examined. The isolates were also found to be resistant to several antibiotics, including chloramphenicol, erythromycin, methicilin, novobiocin penicilin, streptomycin and tetracycline.